Validating the Edinburgh Postnatal Depression Scale Against the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition for Use in Uganda - Atuhaire C; Brennaman L; Nambozi G; Taseera K; Atukunda EC; Ngonzi J; Atwine D; Matthews LT; Rukundo GZ (Dove Medical Press, 2023)
Catherine Atuhaire,1 Laura Brennaman,1 Grace Nambozi,1 Kabanda Taseera,2 Esther C Atukunda,3 Joseph Ngonzi,4 Daniel Atwine,5 Lynn T Matthews,6,7 Godfrey Zari Rukundo8 1Department of Nursing, Mbarara University of Science and Technology, Mbarara, Uganda; 2Department of Microbiology, Mbarara University of Science and Technology, Mbarara, Uganda; 3Department of Pharmacy, Mbarara University of Science and Technology, Mbarara, Uganda; 4Department of Obstetrics & Gynaecology, Mbarara University of Science and Technology, Mbarara, Uganda; 5SOAR Research Foundation, Mbarara, Uganda; 6Division of Infectious Diseases and Center for Global Health Massachusetts General Hospital, Boston, MA, USA; 7Division of Infectious Disease, University of Alabama at Birmingham, Birmingham, AL, USA; 8Department of Psychiatry, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Catherine Atuhaire, Email catuhaire@must.ac.ugBackground: The Edinburgh Postnatal Depression Scale (EPDS) is a widely acknowledged screening tool for postpartum depression (PPD) globally, but its validation in Uganda has been lacking. This study aimed to assess the EPDS's accuracy as a PPD screening tool in Uganda compared to the Mini-International Neuropsychiatric Interview (MINI 7.0.2) based on the DSM-5.Methods: This was a descriptive cross-sectional study conducted at a referral hospital and two peri-urban primary care postpartum clinics in rural southwestern Uganda. We enrolled 287 mothers aged 18 to 49 at their six-week postpartum visit. The EPDS was used for initial screening, and the MINI 7.0.2 was employed for clinical diagnosis. The study used the Runyankore-Rukiga language version of the EPDS and collected data from November 11, 2019, to June 10, 2020, with the MINI 7.0.2 as the reference standard.Results: The overall PPD prevalence was 29.5%, as opposed to 26.5% with EPDS and MINI 7.0.2 DSM-5 criteria (p = 0.239). The EPDS demonstrated a sensitivity of 86.8%, specificity of 92.1%, positive predictive value of 80.5%, and negative predictive value of 94.9%. A cutoff score of ≥ 10 was found to be the most effective acceptable point after drawing the AUC of ROC and determining the most appropriate point using Youden's index. The area under the ROC curve, indicating the scale's overall performance against MINI 7.0.2, was 0.89 for Bwizibwera HCIV, 0.97 for Kinoni HCIV, and 0.84 for MRRH. In conclusion, the EPDS can effectively screen for postpartum depression in southwestern Uganda using a cutoff score of ≥ 10. It exhibits strong diagnostic performance in correctly identifying PPD in postpartum mothers.Keywords: validation, EPDS, DSM-5, MINI, postpartum depression